2011
DOI: 10.1186/1471-2148-11-274
|View full text |Cite
|
Sign up to set email alerts
|

Schmidtea mediterraneaphylogeography: an old species surviving on a few Mediterranean islands?

Abstract: BackgroundSchmidtea mediterranea (Platyhelminthes, Tricladida, Continenticola) is found in scattered localities on a few islands and in coastal areas of the western Mediterranean. Although S. mediterranea is the object of many regeneration studies, little is known about its evolutionary history. Its present distribution has been proposed to stem from the fragmentation and migration of the Corsica-Sardinia microplate during the formation of the western Mediterranean basin, which implies an ancient origin for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 51 publications
2
59
1
2
Order By: Relevance
“…It is worth noting that the molecular analyses revealed a low level of diversification of the group as compared to other Dugesiidae genera of similar age, particularly Dugesia. It is possible that these four species have a recent origin, but molecular trees seem to show an old diversification, which could give support to the idea that they are the remnants of a more widespread diversity (Lazaro et al, 2011).…”
Section: Schmidtea (Ball 1974)mentioning
confidence: 81%
See 1 more Smart Citation
“…It is worth noting that the molecular analyses revealed a low level of diversification of the group as compared to other Dugesiidae genera of similar age, particularly Dugesia. It is possible that these four species have a recent origin, but molecular trees seem to show an old diversification, which could give support to the idea that they are the remnants of a more widespread diversity (Lazaro et al, 2011).…”
Section: Schmidtea (Ball 1974)mentioning
confidence: 81%
“…While there is no specific study analysing the relationships among the Schmidtea species, they have been included in some molecular studies. Such analyses have shown a closer relationship between S. polychroa and S. mediterranea, whereas the relationship between S. lugubris and S. nova is not clear due to the lack of good molecular information for the latter (Álvarez-Presas et al, 2008;Lazaro et al, 2011). It is worth noting that the molecular analyses revealed a low level of diversification of the group as compared to other Dugesiidae genera of similar age, particularly Dugesia.…”
Section: Schmidtea (Ball 1974)mentioning
confidence: 86%
“…In the remaining distribution area, only sexual diploids are found. The molecular study of these populations, based on three markers (Cox1 and cytochrome b (cob) and the 13th nuclear intron of the netrin receptor-like protein gene (N13)), showed that the species is extremely structured [22]. It is divided into three clades that do not share haplotypes, suggesting that the distribution of the species is a consequence of the geological history of the region and it inhabits; its ancestor may have been present in the microplaque that gave rise to the Balearic Islands, Corsica and Sardinia, which implies a quite old age for the species.…”
Section: Species Genetic Structure: Schmidtea Mediterranea and Dugesimentioning
confidence: 99%
“…EF in [31]). The amplified fragment of the ATPase α (also tested in [31]) has a small intron that in the future may be useful for intraspecific analyses, such as the nuclear intron (N13, [22]), which have already proved to be informative for S. mediterranea. Also, in a very recent study, a fragment of the β-actin was used to resolve the phylogeny of a group of planarians from Lake Baikal [43], and it seems to be a good candidate for further molecular studies.…”
Section: Weaknesses Of Molecular Markers and Future Studiesmentioning
confidence: 99%
“…mediterranea is a free-living, freshwater planarian that lives in southern Europe and Tunisia (Lazaro et al 2011;Harrath et al2004). It is a model organism for the research of regeneration and development of tissues such as the brain and germline (Reddien & Sanchez Alvarado 2004;Salo & Baguna 2002).…”
mentioning
confidence: 99%